Development of the multispectral UV polarization reflectance imaging system (MUPRIS) for in situ monitoring of the UV protection efficacy of sunscreen on human skin. Issue 5 (19th March 2019) - Nishino, Ken; Haryu, Yasushi; Kinoshita, Ayui; Nakauchi, Shigeki
Abstract: Background: Protection of the human skin from ultraviolet (UV) damage is one of the main issues in dermatology and cosmetology. The UV protection efficacy (UVPE) of the sunscreen film is decreased by sweat, sebum, and friction during the day. However, the technical relationship between the UVPE evaluated in a laboratory and the actual protection in daily use has not been clarified, because the UVPE measurement method in real‐life setting has not been established. This study aimed to develop a novel UVPE evaluation system that allows in situ monitoring of the UVPE in real‐life activities. Methods: The multispectral UV polarization reflectance imaging system (MUPRIS) and a UVPE estimation algorithm were developed. The diffuse reflectance spectra were measured for a total of 48 sunscreen materials that were applied on 59 subjects. The UVPEs estimated from the diffuse reflectance spectra were compared with the in vivo SPFs. Finally, the UVPE before and after a marine leisure activity was evaluated using the MUPRIS as the practical use test. Results: Compared with the conventional UV camera, the MUPRIS could visualize the applied sunscreen more clearly and showed good UVPE estimation accuracy (correlation coefficient for in vivo SPF, 0.82). In the practical use test, the degradation of the UVPE during a marine leisure activity was quantitatively monitored and was validated by the actual occurrence of sunburn. Conclusions: A novel in situ UVPE monitoring tool had been successfully developed. It can strongly support the development of innovative sunscreen products that can perfectly protect customers against UV irradiation in real‐life situation.